Financial Ratio Analysis and Stock Price Performance of Islamic Banks Listed on the Indonesia Stock Exchange - Wartoyo Wartoyo; Reisya Zahra Munichlakhofa; Makmuri Ahdi (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2025)
The rapid growth of Islamic banking in Indonesia has intensified interest in understanding the financial factors that drive market valuation and investor decision-making. This study aims to analyze the influence of Return on Assets (ROA), Financing to Deposit Ratio (FDR), and Operational Costs to Operational Income (BOPO) on stock prices in Sharia Commercial Banks (BUS) listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. Using a quantitative approach and panel data regression analysis through the Eviews 13 software, this study samples 4 Sharia banks (BTPN Syariah, Bank Aladin Syariah, Bank Panin Dubai Syariah, and Bank Mega Syariah). The results show that partially, Return on Assets (X1) has a positive and significant effect on stock prices with a probability of 0.0007, confirming that profitability is the main attraction for investors. Meanwhile, partially Financing to Deposit Ratio (X2) does not affect stock prices with a probability of 0.3176, indicating that the market tends to be neutral towards the volume of fund distribution and prioritizes liquidity safety aspects. Furthermore, Operational Costs to Operating Income (X3) has a positive and significant effect on stock prices with a probability of 0.0037. This finding shows a unique phenomenon in which the market actually appreciates the increase in operational costs as a form of strategic investment by banks in digital technology transformation to strengthen long-term competitiveness.